Prioritization of invasive alien species with the potential to threaten agriculture and biodiversity in Kenya through horizon scanning - Mulema, Joseph; Day, Roger; Nunda, Winnie; Akutse, Komivi Senyo; Bruce, Anani Yaovi; Gachamba, Sospeter; Haukeland, Solveig; Kahuthia-Gathu, Ruth; Kibet, Staline; Koech, Asenath; Kosiom, Thomas; Miano, Douglas; et al. (Springer, 2022)
Invasive alien species (IAS) rank among the most significant drivers of species extinction and ecosystem degradation resulting in significant impacts on socio-economic development. The recent exponential spread of IAS in most of Africa is attributed to poor border biosecurity due to porous borders that have failed to prevent initial introductions. In addition, countries lack adequate information about potential invasions and have limited capacity to reduce the risk of invasions. Horizon scanning is an approach that prioritises the risks of potential IAS through rapid assessments. A group of 28 subject matter experts used an adapted methodology to assess 1700 potential IAS on a 5-point scale for the likelihood of entry and establishment, potential socio-economic impact, and impact on biodiversity. The individual scores were combined to rank the species according to their overall potential risk for the country. Confidence in individual and overall scores was recorded on a 3-point scale. This resulted in a priority list of 120 potential IAS (70 arthropods, 9 nematodes, 15 bacteria, 19 fungi/chromist, 1 viroid, and 6 viruses). Options for risk mitigation such as full pest risk analysis and detection surveys were suggested for prioritised species while species for which no immediate action was suggested, were added to the plant health risk register and a recommendation was made to regularly monitor the change in risk. By prioritising risks, horizon scanning guides resource allocation to interventions that are most likely to reduce risk and is very useful to National Plant Protection Organisations and other relevant stakeholders.